Cell-bound helper and suppressor factors in primate lymphocytes. - Lehner, T (1982)
Cell-bound helper and suppressor factors, on lymphocytes from Rhesus monkeys, were assayed by the indirect immunofluorescent method, using F(ab')2 fragments of rabbit antisera to antigen specific secreted helper and suppressor factors. The rabbit antisera recognize the function related to the 'constant' region of secreted antigen specific helper or suppressor factor. Immunoadsorption studies suggest that the two antisera also recognize cell surface markers of helper or suppressor cell, for the activity of the anti-helper factor (HF) antiserum was adsorbed by cells from helper cell but not by suppressor cell induction cultures and the converse was found for the anti-suppressor factor (SF) antiserum. A significantly greater proportion of bound SF than HF was found in lymphocytes from controls and the converse or a greater proportion of HF and SF was found in lymphocytes from immunized monkeys. Furthermore, a significantly greater proportion of T-enriched cells bound anti-SF than anti-HF and the converse was found with T-depleted cells, suggesting that the assay detects the target cell as well as the cell of origin of these factors. A sequential in vitro comparison of cell-bound and secreted factors revealed that the highest number of cells which stained with anti-HF was on day 4 of the culture and this correlated with the highest secreted HF activity. However, cells which stained with anti-SF reached a peak on day 2, whereas maximal secreted SF activity was found on day 3. In vivo the kinetic relationships after immunization showed similar timings for the development of bound HF and SF, though the proportion of cells differed. However, the secreted HF after secondary immunization reached its highest level of activity on day 5, as compared with day 2 for cell bound HF. Both primary and secondary cellular but not antibody responses showed well defined bi-phasic responses and their significance as well as those of bound HF and SF in immunoregulation will need to be explored further.